Effectiveness of Bowen Intergenerational Family Therapy on Marital Conflicts and Interpersonal Forgiveness - Bustin , Somayeh; Mirzaei , Seyed Hossein; Ghasemi Motlagh , Mehdi (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The objective of this study was to evaluate the effectiveness of Bowen intergenerational family therapy on reducing marital conflicts and enhancing interpersonal forgiveness.Methodology: This research employed a quasi-experimental design with pre-test, post-test, and follow-up phases, incorporating a control group. The statistical population consisted of families who visited the counseling and psychology center in District 1 of Karaj in 2023. Eight families were selected through convenience and voluntary sampling and were randomly assigned to experimental and control groups, each comprising four families. Data were collected using the Differentiation of Self Inventory, the Forgiveness Questionnaire, and the Marital Conflict Questionnaire. The intervention, based on Bowen intergenerational therapy, was conducted over eight weekly group sessions, each lasting 90 minutes. Data analysis involved univariate and multivariate covariance analyses using SPSS software.Findings: The findings revealed that Bowen intergenerational therapy significantly impacted both marital conflicts and interpersonal forgiveness. Specifically, the experimental group showed a marked decrease in marital conflict scores from 154.1 (SD = 11.3) in the pre-test to 139.4 (SD = 10.9) in the post-test, which remained stable at 139.2 (SD = 10.3) in the follow-up phase. Similarly, interpersonal forgiveness scores increased from 78.4 (SD = 5.7) in the pre-test to 114.2 (SD = 9.9) in the post-test and remained at 111.1 (SD = 8.9) during the follow-up phase. These changes were statistically significant compared to the control group, which showed no significant changes.Conclusion: The study concludes that Bowen intergenerational family therapy is effective in reducing marital conflicts and enhancing interpersonal forgiveness. The findings align with previous research, underscoring the therapy's potential to address relational issues and improve emotional regulation within families.